Precarious Ties: Business and the State in Authoritarian Asia - Jia, Ruixue (Journal of Economic Literature, 2024)
Ruixue Jia of University of California, San Diego reviews “Precarious Ties: Business and the State in Authoritarian Asia” by Meg Rithmire. The Econlit abstract of this book begins: “Examines trust and financial control at work in creating patterns of state-business relations in Malaysia, Indonesia, and China, exploring the strategies that authoritarian political elites adopt to manage the business class.”